The Influence of Service Quality on Customer Satisfaction and Its Impact on Repurchase Interests in Telkomcell Products in Timor Leste - Carlos Soares Ribeiro; Diane Indiyati (Ridwan Institute, 2023)
Telkomcel's customers started to complain and lost their trust and their customers got worse and worse. In order to take back the customer's trust, Telkomcel implemented two main strategies, namely the Push Strategy and the Pull Strategy in its marketing activities. This study aims to provide an overview of Specific Service Quality in three dimensions, namely Tangible, Empathy and Assurance, Customer Satisfaction and Repurchase Intention at Telkomcel Timor Leste, and to determine the effect of service quality on Repurchase Intention with customer satisfaction interventions at Telkomcel East Timor. Based on the results of distributing questionnaires to 200 people at several universities in Timor Leste such as UNTL (Timor Loro Sae National University), UNPAZ (Universidade Da Paz), UNITAL (Universidade de Oriental) and DIT (Dili Institute of Business) ISC (Institut Unggul Cristal) 200 students, lecturers and administrative staff on campus randomly using a Likert scale and non-probability sampling techniques and purposive sampling. SEM (Structural Equation Modeling) data analysis technique, with the help of SmartPLS 3.0 software.